2010
DOI: 10.1377/hlthaff.2010.0305
|View full text |Cite
|
Sign up to set email alerts
|

If You Build It, Will They Come? Designing Truly Patient-Centered Health Care

Abstract: As the United States debates how to reorganize its health care system, policy makers must ask what patients really want and need from their primary care providers. There is often a disconnect between what patients say they want and what other providers or payers think patients want. Our research at the National Partnership for Women and Families suggests that a truly patient-centered health care system must be designed to incorporate features that matter to patients--including "whole person" care, comprehensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
114
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(117 citation statements)
references
References 10 publications
3
114
0
Order By: Relevance
“…Effectively implementing patient-centered care requires a thorough evaluation of its impact on patients, including an understanding of patients' perceptions [14][15]. In an analysis of health care organizations that implemented patient-centered care initiatives, Luxford and colleagues found that going beyond conventional frameworks to engage patients was essential [16].…”
Section: Introductionmentioning
confidence: 99%
“…Effectively implementing patient-centered care requires a thorough evaluation of its impact on patients, including an understanding of patients' perceptions [14][15]. In an analysis of health care organizations that implemented patient-centered care initiatives, Luxford and colleagues found that going beyond conventional frameworks to engage patients was essential [16].…”
Section: Introductionmentioning
confidence: 99%
“…PCC encompasses a number of key concepts, each capturing a distinct measurable facet of the patient health care experience that can be directly assessed. These concepts include: patient activation; 6,7 shared patient/provider decisionmaking; 8,9 empathy and holistic care in the patient-provider relationship; 6,7 chronic care delivery; 10 and timely, accessible care that meets patient's needs, preferences, and results in optimal satisfaction. 6,9 A variety of measures can be used to assess impacts of PCC and patient experiences on health care quality, including preventive care screenings, e.g., breast, cervical and colorectal cancer screening; 11 chronic condition care and management, e.g., appropriate tests of (and abnormal tests results for) common chronic conditions like diabetes [11][12][13][14] and hypertension; [11][12][13] and emergency room (ER) and inpatient (IP)…”
mentioning
confidence: 99%
“…4 Patients want their clinicians to take a holistic, rather than a disease-based, approach to their care and coordinate and communicate it across care settings. 92 The current system of uncoordinated, sequential visits to multiple clinicians, departments and specialties works against value. Instead, integrated, team-based practice units are needed that encompass all essential skills and services required over the full cycle of care for common medical conditions and their related comorbidities.…”
Section: Convert Health Care Institutions Into Rapidly Learning Organmentioning
confidence: 99%